2015
DOI: 10.1021/acsphotonics.5b00132
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Semiconductor Phased-Array Metasurfaces

Abstract: Phased array metamaterial systems are enabling new classes of refractive and diffractive optical elements through spatial-phase engineering. In this letter, we develop design principles for reconfigurable optical antennas and metasurfaces. We theoretically demonstrate tunability of infrared scattering phase and radiation patterns in low-loss, high index dielectric resonators using free carrier refraction. We demonstrate reconfigurable endfire antennas based on interference between multiple elements. Within sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 74 publications
4
86
0
Order By: Relevance
“…It was shown that the electric resonance has a larger tuning range because of the extending fringing field outside the resonators, while the magnetic resonance has minimal tuning capability because of the well-confined field distribution within the dielectric resonators. Reconfigurable directional scattering can be also accomplished using metasurfaces comprised of semiconducting resonator arrays through injection of free charge carriers by optical excitation [144].…”
Section: Directional Scatteringmentioning
confidence: 99%
“…It was shown that the electric resonance has a larger tuning range because of the extending fringing field outside the resonators, while the magnetic resonance has minimal tuning capability because of the well-confined field distribution within the dielectric resonators. Reconfigurable directional scattering can be also accomplished using metasurfaces comprised of semiconducting resonator arrays through injection of free charge carriers by optical excitation [144].…”
Section: Directional Scatteringmentioning
confidence: 99%
“…Our design ultimately requires suffi cient width to incorporate metallic electrodes in these side regions of low E-fi eld intensity; throughout this paper we use 3 μm wide resonators. Since introducing free-carriers causes a resonance blueshift, [ 36 ] we design the initial resonance wavelength (13.5 μm) red shifted with respect to the operating wavelength (11.35 μm) by selecting a resonator height of 1 μm.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
“…spherical InSb Mie resonators [ 36 ] showed that the index change (Δ n ≈ 2 based on Drude model) from a doping concentration of 1.5 × 10 18 cm −3 was suffi cient to obtain 2π phase shifts. We use a worst-case Drude scattering rate of 2 THz, reported for highly doped InSb, [ 32 ] for all carrier densities.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, implementation of plasmonic principles for developing of all-dielectric nonlinear nanodevices looks tempting. Recently, the enhancement of optical nonlinearities in resonant Si nanostructures has been demonstrated theoretically and experimentally at the scale of single nanoparticles [58][59][60][61][194][195][196][197].…”
Section: F Nonlinear Nanophotonics Applicationsmentioning
confidence: 99%